2003
DOI: 10.1152/ajplung.00077.2002
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibition by ω-3 fatty acids modulates LPS-stimulated macrophage TNF-α transcription

Abstract: Omega-3 fatty acid (FA) emulsions reduce LPS-stimulated murine macrophage TNF-alpha production, but the exact mechanism has yet to be defined. The purpose of this study was to determine the mechanism for omega-3 FA inhibition of macrophage TNF-alpha production following LPS stimulation. RAW 264.7 cells were pretreated with isocaloric emulsions of omega-3 FA (Omegaven), omega-6 FA (Lipovenos), or DMEM and subsequently exposed to LPS. IkappaB-alpha and phospho-IkappaB-alpha were determined by Western blotting. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
240
1
14

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(281 citation statements)
references
References 23 publications
23
240
1
14
Order By: Relevance
“…Our results are in accord with Poerschmann et al, who showed that the unsaturation index of FAs in algae and bacteria tends to be higher in colder climates than in warmer climates [70,74]. -3 PUFAs, but not -6 PUFAs, mono-unsaturated FAs or saturated FAs, have been shown to be potent NF-B inhibitors [75][76][77][78][79][80]. One would hence have expected the CCMP 1619 extract, which has a twelve times higher concentration in -3 PUFA than the remaining extracts, to stand out as the strongest NF-B inhibitor.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accord with Poerschmann et al, who showed that the unsaturation index of FAs in algae and bacteria tends to be higher in colder climates than in warmer climates [70,74]. -3 PUFAs, but not -6 PUFAs, mono-unsaturated FAs or saturated FAs, have been shown to be potent NF-B inhibitors [75][76][77][78][79][80]. One would hence have expected the CCMP 1619 extract, which has a twelve times higher concentration in -3 PUFA than the remaining extracts, to stand out as the strongest NF-B inhibitor.…”
Section: Discussionsupporting
confidence: 93%
“…We have shown EPA to prevent both degradation of I-kBa and nuclear accumulation of NF-kB in murine myotubes in the presence of PIF , through attenuation of upstream signalling pathways. Omega-3 polyunsaturated fatty acids have also been shown to inhibit I-kB phosphorylation and NF-kB activation in murine macrophages, although the mechanism is not known (Novak et al, 2003). This manuscript provides experimental evidence to support the claim that PIF induces proteasome expression through activation of nuclear binding of NF-kB.…”
Section: Discussionmentioning
confidence: 65%
“…Thus EPA, which prevents nuclear migration of NF-kB in murine myotubes in response to PIF by stabilising the cytosolic I-kB/NF-kB complex (Whitehouse and Tisdale, 2003), possibly by interfering with I-kB phosphorylation (Novak et al, 2003), has been shown to attenuate the development of further weight loss in weight-losing patients with pancreatic cancer (Wigmore et al, 2000) and produce an increase in lean body mass when combined with a high protein energy dense nutritional supplement (Barber et al, 1999). The anti-inflammatory agent, ibuprofen, has been shown to inhibit constitutive activation of NFkB and IKKa in prostate cancer cells (Palayoor et al, 1999), and when combined with megestrol acetate produced an increase in body weight in gastrointestinal cancer patients (McMillan et al, 1999), while megestrol acetate alone produced a decrease in body weight.…”
Section: Discussionmentioning
confidence: 99%